2005
DOI: 10.1007/s10546-004-5940-0
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Ekman Layer Approximation for Smooth Eddy Diffusivity Profiles

Abstract: The Ekman boundary-layer model is extended analytically for a gradually varying eddy diffusivity K(z) ! 0, z ! 0. A solution for the Ekman layer is provided having similar structure to the constant-K case; that is, exponentially decaying sine functions for the two horizontal wind components. The analytical asymptotic solution compares well with its numerical counterpart for various K(z). The result can be useful in theoretical studies such as Ekman pumping, for efficient estimation of the Ekman layer profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Within the WKB(J) theory (e.g. Bender and Orszag, 1978;Grisogono, 1995;Oerlemans, 2001a, 2001b;Parmhed et al, 2005), the angle α 0 will be shown to largely concur with that from SH09 and van Ulden and Holtslag (1985). To reword, the angle α 0 ∼ 35 • will be estimated analytically in this study.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Within the WKB(J) theory (e.g. Bender and Orszag, 1978;Grisogono, 1995;Oerlemans, 2001a, 2001b;Parmhed et al, 2005), the angle α 0 will be shown to largely concur with that from SH09 and van Ulden and Holtslag (1985). To reword, the angle α 0 ∼ 35 • will be estimated analytically in this study.…”
Section: Introductionmentioning
confidence: 65%
“…(3) allows for gradual variations of the previously introduced I(z) = {f /(2K)} 1/2 z by simply integrating K(z) vertically (Grisogono, 1995). This is the essence of the WKB method for boundary-layer flows (Bender and Orszag, 1978;Berger and Grisogono, 1998;Parmhed et al, 2005). Now, various reasonably smooth profiles may be deployed in Eq.…”
Section: Gradually Varying Eddy Diffusivity K(z)mentioning
confidence: 99%
“…However, this solution is unphysical both at the surface and at the interface with the free tropospheric flow, and several alternative analytical solutions with more realistic functions for the eddy coefficient can be found in the literature (e.g. Nieuwstadt 1985;Grisogono and Oerlemans 2001;Tan 2001;Parmhed et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Of course, other choices are possible depending on specific cases addressed. Further details on estimating K max and h can be found in Grisogono and Oerlemans (2002) and Parmhed et al (2004); Parmhed et al (2005).…”
Section: The Wkb Solutionsmentioning
confidence: 99%
“…Additional remarks on how to estimate the input parameters for this Ekman-Prandtl model type with K(z) can be found in Parmhed et al (2004); Parmhed et al (2005). The new analytical solutions (U, V, θ) WKB , (16), (17) and (18) are not named "asymptotic", which usually holds for the WKB solutions, only because we weakly decoupled (2) so that V WKB does not feed back to the original system (1)-(3).…”
Section: Comparison With the Numerical And Constant-k Solutionsmentioning
confidence: 99%